Gulo gulo - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Gulo gulo (Linnaeus 1758) [Mustela] gulo Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 45. Type Locality: "alpibus Lapponiæ, Ruffiae, Sibiriae, sylvis vastissimis", restricted by Thomas (1911 a ) to "Lapland". Vernacular Names: Wolverine. Subspecies:: Subspecies Gulo gulo subsp. gulo Linnaeus 1758 Subspecies Gulo gulo subsp. albus (Kerr 1702) Subspecies Gulo gulo subsp. katschemakensis Matschie 1918 Subspecies Gulo gulo subsp. luscus Linnaeus 1758 Subspecies Gulo gulo subsp. luteus Elliot 1904 Subspecies Gulo gulo subsp. vancouverensis Goldman 1935 Distribution: Canada, China (Heilongiang, Xinjiang, Inner Mongolia), Finland, Mongolia, Norway, Russia, Sweden, USA (Alaska, Wyoming, Idaho, Montana). Conservation: IUCN – Vulnerable. Discussion: Degerbøl (1935) and Kurtén and Rausch (1959) demonstrated that gulo and luscus are conspecific. Reviewed by Pasitschniak-Arts and Larivière (1995). Synonyms allocated according to Ellerman and Morrison-Scott (1951) and Pasitschniak-Arts and Larivière (1995). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 607, DOI: 10.5281/zenodo.7316519